2009
DOI: 10.1002/da.20473
|View full text |Cite
|
Sign up to set email alerts
|

Negative affectivity in smokers applying to smoking cessation clinics: a case-control study

Abstract: Smokers applying to smoking cessation clinics for the first time have a higher level of negative affectivity than smokers from the general population. An evaluation of the level of negative affectivity could be introduced into clinical practice to have a complete assessment of the patient. We propose adding psychological or pharmacological support to complement the smoking cessation program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 58 publications
0
9
0
1
Order By: Relevance
“…In addition, Ng et al [36] demonstrated that physical activity was efficacious for reducing depression and anxiety. In research on the effectiveness of cessation programs for the general population of smokers, Faulkner et al [37] provide preliminary support for the effectiveness of a physical activity program for helping smokers to quit, and Cosci et al [38] have proposed adding psychological or pharmacological support to complement smoking cessation programs. Thus, the introduction of a physical activity program alongside health promotional education might be important for the prevention of lifestyle-related diseases in patients with mood disorders, in the recovery stage when the depressive symptoms are decreasing.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Ng et al [36] demonstrated that physical activity was efficacious for reducing depression and anxiety. In research on the effectiveness of cessation programs for the general population of smokers, Faulkner et al [37] provide preliminary support for the effectiveness of a physical activity program for helping smokers to quit, and Cosci et al [38] have proposed adding psychological or pharmacological support to complement smoking cessation programs. Thus, the introduction of a physical activity program alongside health promotional education might be important for the prevention of lifestyle-related diseases in patients with mood disorders, in the recovery stage when the depressive symptoms are decreasing.…”
Section: Discussionmentioning
confidence: 99%
“…The results initially confirmed previous findings that smokers score higher in measures of negative affect than nonsmokers. 3,7,[17][18][19][20][21] Another aspect investigated was the element Attachment to Cigarettes, which unpublished observations of our group suggest to be a true measurement of the connection between smokers and their object of addiction.…”
Section: Discussionmentioning
confidence: 99%
“…The median values of SET evaluated in the two occasions were, respectively, 6.5 (3-17) and 7 (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). The value of the ICC was 0.944.…”
Section: Reliabilitymentioning
confidence: 90%
See 1 more Smart Citation
“…Studies in the literature have shown an increase in negative affects in smokers, (26,27) as well as high levels of anxiety and depression in those who are about to enter a smoking cessation program. (28,29) The fact that our facility is a referral center for smoking cessation might have influenced the smokers evaluated in the present study to seek treatment there, those individuals having high levels of anxiety and depression, which were primarily due to failed attempts to quit smoking.…”
Section: Discussionmentioning
confidence: 99%